When data don't drive: teacher agency in data use efforts in low-performing schools. Issue 2 (2nd April 2020) - Lockton, Marie; Weddle, Hayley; Datnow, Amanda
ABSTRACT: Grounded in the belief that data will drive instructional change, data-driven decision making continues to be a prevalent reform strategy in schools. However, the use of data does not always prompt teachers to change their instructional practices, particularly in low-performing schools where accountability pressures loom large. Drawing on in-depth qualitative data gathered in 4 middle schools, we explore the questions: What is the interplay of teacher agency with the structure and culture of data use in schools? How do teachers exercise agency in efforts to use data for instructional change in low-performing schools? We found that within prevailing accountability frameworks, teachers exercised agency to bridge structural and cultural gaps between data use and instructional improvement; yet, their efforts were kept largely on the periphery. Implications for policy and research are discussed.